Analisis Faktor Convenience, Design, Trustworthiness, Price dan Various Food Choices Terhadap Intention To Continously Use Melalui Perceived Value dan Attitude Towards Food Delivery Apps pada Pelanggan Gofood di Manado - Felicia Veronica Wagiu; Ronald; Amelia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In the current era of the industrial revolution, it has brought about fundamental changes in various area global order of life. This is characterized by the increasing development of innovation and creativity in information technology which is disrupting various aspects of global life, including competition in the economic sector. This disruption can be reflected in rapid changes that provide momentum to make entrepreneurship the front guard of winning global economic competition. Some industries have opportunities for rapid growth while other industries may experience a decline in the rapid development of Information and Communication Technology which has an impact on socio-economic conditions. This concept is a view of the interaction between the development of innovation and technological development which has implications for macro and micro economics. Among the sectors affected are products and services that are being developed, the production, sale or supply of which depends on how far digital technology reaches. In the digital economy, companies offer their services according to special services for special requests or special offers whose offerings are characterized as. This research was appointed to analyze the influence of convenience, design, trustworthiness, price, various food choices towards intention to continue use through perceived value and attitude towards food delivery apps, especially Gofood customers in Manado. The sample used in this research was Gofood customers in Manado based on data from 120 respondents. For data processing and analysis in this research, we use Structural Equation Modeling (SEM) with AMOS20.0 software as software for processing data.In this research it was found that satisfaction has a positive value towards intention continuously to use so that the higher level of customer satisfaction results in stronger customers using the Gofood application in Manado.